Activity of Trigonella foenum-graecum on Some Cell Lines. - Agustini, Kurnia; Sumaryono, Wahono; Widyanto, R Micho (Indonesian Journal of Cancer Chemoprevention, 2011)
TrigonellaÃÂ  foenum-graecumÃÂ  (TFG)ÃÂ  isÃÂ  oneÃÂ  ofÃÂ  medicinalÃÂ  plantsÃÂ  containsÃÂ  some steroidal sapogeninÃÂ  such as diosgenin, yamogenin, gitogenin, tigogenin and trigoneoside, alsoÃÂ  alkaloidÃÂ  trigonellin,ÃÂ  whichÃÂ  isÃÂ  haveÃÂ  manyÃÂ  activityÃÂ  asÃÂ  antidiabetic,ÃÂ  estrogenicÃÂ  andÃÂ  also asÃÂ  antiÃÂ  cancer.ÃÂ ÃÂ ÃÂ  ThisÃÂ  experimentÃÂ  wasÃÂ  doneÃÂ  toÃÂ  exploreÃÂ  theÃÂ  activityÃÂ  ofÃÂ  someÃÂ  extractÃÂ  of TFG on some cell lines such as MCF7 (Human Breast Cancer Cell-line), T47D (Human BreastÃÂ  CancerÃÂ  Cell-line),ÃÂ  PC3ÃÂ  (HumanÃÂ  ProstateÃÂ  Cell-line)ÃÂ  andÃÂ  SKOVÃÂ  (HumanÃÂ  Ovarian Carcinoma Cell-line).ÃÂ  This assay was done using MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium)ÃÂ  methods.ÃÂ ÃÂ ÃÂ  ResultsÃÂ  showedÃÂ  thatÃÂ  ethylÃÂ  acetateÃÂ  fractionÃÂ  givesÃÂ  the lowestÃÂ  IC50ÃÂ  thanÃÂ  anotherÃÂ  extracts.ÃÂ  IC50ÃÂ  forÃÂ  PC3ÃÂ  isÃÂ  66.24ÃÂ  ppm,ÃÂ  IC50ÃÂ  forÃÂ  MCF7ÃÂ  isÃÂ  41.81 ppm,ÃÂ  IC50ÃÂ  forÃÂ  T47DÃÂ  isÃÂ  58.63ÃÂ  ppm.ÃÂ ÃÂ ÃÂ  TheseÃÂ  datasÃÂ  canÃÂ  beÃÂ  usedÃÂ  forÃÂ  furtherÃÂ  researchÃÂ  to isolate the active compound from TFG. Keywords: Trigonella foenum-graecum, MCF-7, T47D, SKOV, PC3.